2005
DOI: 10.1016/j.plantsci.2004.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt on lipid peroxidation and antioxidant enzyme activities of Catharanthus roseus suspension cells

Abstract: Cells of Catharanthus roseus (L.) G. Don were maintained and sub-cultured in the absence of NaCl (control) or were sub-cultured for 7 days in the presence of 50 ("50") or 100 ("100") mM NaCl, or were maintained and sub-cultured for 8 months in the continuous presence of 50 mM NaCl ("50T" or salt-adapted cells). Exposure to salt treatment reduced growth in a concentration-dependent manner. Salt-treated cells strongly accumulated Na + and, to a lesser extent, Cl -. However, no significant change in Claccumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
74
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 46 publications
13
74
1
1
Order By: Relevance
“…Lipid Peroxidation (LP) is associated with damages provoked by a variety of environmental stresses. Poly-Unsaturated Fatty Acids (PUFA) are the main membrane lipid components susceptible to peroxidation and degradation (Elkahoui et al, 2005). The increase in LP, as caused by NaCl stress in the present study, can be correlated to ion accumulation and AOS production under salt stress (Hernandez et al, 2000).…”
Section: Discussionmentioning
confidence: 51%
“…Lipid Peroxidation (LP) is associated with damages provoked by a variety of environmental stresses. Poly-Unsaturated Fatty Acids (PUFA) are the main membrane lipid components susceptible to peroxidation and degradation (Elkahoui et al, 2005). The increase in LP, as caused by NaCl stress in the present study, can be correlated to ion accumulation and AOS production under salt stress (Hernandez et al, 2000).…”
Section: Discussionmentioning
confidence: 51%
“…These results agree with previous results obtained in fruits of tomato cultivar Raissa, where water stress caused a significant increase in H 2 O 2 and MDA contents of fruits (Murshed et al 2008a). Under abiotic stress environments, the plant lipid metabolism is interrupted as a result of oxidative damage to membrane lipids by ROS and lipid peroxidation (Elkahoui et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to cell culture growth, it was observed that under normal conditions, P. pinaster suspension cells evidenced exponential growth and an absent lag phase, a behaviour already observed in other suspension cell models (Shimon-Kerner et al, 2000). Increasing concentrations of salt resulted in growth inhibition and eventual arrest, as expected from previous reports (Elkahouia et al, 2005). A concentration of 100 mM NaCl was subsequently chosen to impose severe salt stress without preventing cell growth.…”
Section: Discussionmentioning
confidence: 69%
“…Overexpression of various isoforms of SOD has been shown to confer improved tolerance to oxidative stress (Bowler et al, 1991;Perl et al, 1993). Moreover, overexpression of SOD and APX isozymes has been previously co-related with salt tolerance (Kaminaka et al, 1999;Wang et al, 1999), and the involvement of APX in the mechanisms of salt tolerance has also been substantiated at protein level (Elkahouia et al, 2005;Koca et al, 2007;Masood et al, 2006). Finally, present results are corroborated by microarray transcript profiling of salt-challenged Arabidopsis plants, in which all three Fe-SOD, but none other SOD isoform, presented induced expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation